2004
DOI: 10.1086/502379
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Based Handrub: Evaluation of Technique and Microbiological Efficacy with International Infection Control Professionals

Abstract: BACKGROUND AND OBJECTIVE:The Centers for Disease Control and Prevention has published a new guideline on hand hygiene promoting the use of the alcohol-based handrub, but the technique was not addressed. The goal of this study was to evaluate the influence of technique on the efficacy of the alcohol-based handrub.PARTICIPANTS: Healthcare workers (HCWs) attending a course in hospital epidemiology.METHODS: A fluorescent dye was added to a hand antiseptic, and hands were checked under ultraviolet light after antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…[1][2][3] In the past few years, important advances have been achieved in the field that may have had an impact on the reduction of SSIs. 4 These include more effective surgical sterilization procedures, laminar flow, high-efficiency particulate absorbing (HEPA) filters, ultraviolet radiation, air renewal, humidity control, differential temperature and air pressure, particle count, surface colony count and antibiotic prophylaxis. [5][6][7][8] However, other factors, such as decreased length of hospital stay, and more aggressive interventions performed on patients with worse clinical conditions, probably contribute to an increased incidence of SSIs.…”
mentioning
confidence: 99%
“…[1][2][3] In the past few years, important advances have been achieved in the field that may have had an impact on the reduction of SSIs. 4 These include more effective surgical sterilization procedures, laminar flow, high-efficiency particulate absorbing (HEPA) filters, ultraviolet radiation, air renewal, humidity control, differential temperature and air pressure, particle count, surface colony count and antibiotic prophylaxis. [5][6][7][8] However, other factors, such as decreased length of hospital stay, and more aggressive interventions performed on patients with worse clinical conditions, probably contribute to an increased incidence of SSIs.…”
mentioning
confidence: 99%
“…Put simply, the closer the alcohol-based handrub to the point of indication of use, such as the end of the patient bed or on the wall in each clinical care area, directly influences practice. Furthermore, research has shown that it saves time, and preliminary data reported by Widmer and colleagues 14,15 demonstrate better compliance than handwashing.…”
mentioning
confidence: 99%
“…B. mit fluoreszierendem Farbstoff im HDM [383] zu gewährleisten. Im Rahmen dieser Schulungen ist es zu empfehlen, dass die Verbrauchsdaten für HDM innerhalb der Organisationseinheiten bewertet werden.…”
Section: Technikunclassified